Autophagy and LC3-associated phagocytosis: similarities and differences - B. R. Ibragimov; Yu. V. Skibo; Z. I. Abramova (Медицинская иммунология, 2023)
Previously, autophagy was termed as a mechanism used by the cells with a lack of essential nutrients supporting homeostasis. Over the decade of studies, autophagy proved to be a more complex, ambiguous mechanism. Its activation depends on the nature of stimulus, type of immune cells and the final result. Both canonical and non-canonical autophagy, being similar in molecular events, but showing their own distinctive features, are key processes in protecting the body from penetration of intracellular pathogens, maintaining the required level of nutrients in the cell, and removing damaged organelles and cells. Canonical autophagy probably evolved as a homeostatic response to cellular stress and nutritional deficiencies, whereas non-canonical autophagy emerged as a response to suppression of inflammation. Non-canonical autophagy, hereinafter referred to as LC3-associated phagocytosis (LAP), combines the molecular mechanism of phagocytosis with an autophagy mechanism characterized by ingestion of exogenous pathogens, formation of phagosomes (laposomes) and enhanced fusion with lysosomes, followed by degradation of their contents.Significant differences were found between the processes of LAP- and canonical autophagy, which are similar in its mechanism of action. The presence of PI3K complexes in both processes, utilization and intracellular degradation of the “cargo” which is not required for the cells and organism proceeding in the lysosomes, and involvement of almost the same proteins provide similarity of their mechanisms. However, there are differences in the initiation of the processes, e.g., different types of PI3K complexes (in autophagy, PI3K III class 1 and 2 types; in LAP PI3K III, class 3 type), usage of reactive oxygen species in LAP, different types of regulatory proteins involved (ULK1, FIP200, ATG13 , Ambra1, WIPI2, ATG14 in autophagy; and Rubicon and NOX2 in LC3-associated phagocytosis), different number of layers in the membrane structure in which lysis occurs (double-membrane autophagolysosome and single-layer membrane in laposomes) clearly depict the variety of canonical and non-canonical autophagy. The two pathways are directed for different types of biological objects, i.e., intracellular pathogens, dysfunctional proteins and organelles in autophagy, and extracellular pathogens, apoptotic bodies, bacteria, utilized in LAP, thus making these mechanisms completely different in their significance.Collectively, the new data indicate that autophagy performed via both canonical and non-canonical pathways, has evolved into a host defense mechanism capable of resisting immunological and pathogenic stress and mediating immunological tolerance to both intra- and extracellular threats. The present review discusses fundamental molecular differences between these mechanisms, as well as their role in immunity, based on the latest literature data.